Environmental factors influencing the transmission of Haemonchus contortus - Santos, Michelle C. [UNESP]; Silva, Bruna F. [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (Elsevier B.V., 2012)
Infection with the gastrointestinal nematode Haemonchus contortus causes considerable losses in the sheep industry. In this study, we evaluated the effect that climate has on third-stage larvae (L3) of H. contortus in terms of their migration from sheep feces to Brachiaria decumbens grass, as well as their distribution among the forage plants. Fecal samples containing H. contortus L3 was deposited on the soil among the herbage at an initial height of 30 cm. Sample collection began 24 h after contamination and was performed on alternate days over 13 days. The L3 were recovered and quantified in three strata (heights) of grass (0-10 cm, 10-20 cm and >20 cm) as well as in the remaining feces and a superficial layer of soil, collected from beneath the feces. In order to obtain results under different environmental conditions, fecal samples containing H. contortus L3 were deposited on pasture in January (summer), in April (autumn), and July (winter). In all of the periods, the L3 were able to migrate from the feces to the herbage. However, rains, accompanied by high relative humidity and high temperatures, apparently favored migration. The highest L3 recovery rate in the pasture was in the summer observation period, which had the highest number of days with measurable precipitation, high relative humidity (>68.2%), and the highest temperatures at the soil level (minimum and maximum means of 19 degrees C and 42 degrees C, respectively). Under those conditions, larvae began to reach the upper stratum of the grass (>20 cm) by 24h after the deposition of fecal matter, the number of larvae having reached that stratum peaking at seven days after deposition. In the autumn observation period, there was no rainfall in the first five days post-contamination. During that period, high numbers of larvae were found in the fecal samples demonstrating that feces can act as a reservoir of larvae in the absence of rain. Except for two days in the summer observation period, when most of the L3 were recovered from the tops of blades of grass, L3 where located predominantly at the base of the herbage. In conclusion, rainfall favors the migration of L3 from feces to herbage. In addition, larval migration up and along blades of grass can occur relatively rapidly when the temperature is high. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Epidemiology; Herbage; Nematoda; Sheep; Parasitic gastroenteritis